2019
DOI: 10.4315/0362-028x.jfp-18-245
|View full text |Cite
|
Sign up to set email alerts
|

Motivators and Barriers to Cooking and Refrigerator Thermometer Use among Consumers and Food Workers: A Review

Abstract: Temperature control prevents the rapid growth of foodborne pathogens during food storage and assures adequate heating to destroy pathogens prior to consumption. The use of thermometers is a recognized best practice among consumer and food worker guidelines; however, compliance with this recommendation is quite low. Eighty-five studies from the past 21 years were reviewed and an analyzed for the knowledge, attitudes, and behaviors associated with thermometer use and the motivators and barriers to cooking and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 102 publications
2
33
1
Order By: Relevance
“…The absence of thermometer-use during cooking highlight possible food safety concerns because cooking is a crucial factor in preventing foodborne diseases (Kennedy et al, 2011). Previous studies have highlighted the importance of thermometer-use, especially when cooking raw meat or poultry in order to achieve the recommended temperature (Green and Selman, 2005;Lelieveld et al, 2016;Feng and Bruhn, 2019). In a study by Phang and Bruhn (2011), it was reported that at least 30% of the respondents tend to undercook meat.…”
Section: Current Temperature Control Practices During Cookingmentioning
confidence: 99%
See 4 more Smart Citations
“…The absence of thermometer-use during cooking highlight possible food safety concerns because cooking is a crucial factor in preventing foodborne diseases (Kennedy et al, 2011). Previous studies have highlighted the importance of thermometer-use, especially when cooking raw meat or poultry in order to achieve the recommended temperature (Green and Selman, 2005;Lelieveld et al, 2016;Feng and Bruhn, 2019). In a study by Phang and Bruhn (2011), it was reported that at least 30% of the respondents tend to undercook meat.…”
Section: Current Temperature Control Practices During Cookingmentioning
confidence: 99%
“…Many food handlers were unaware that food should be cooked properly according to recommended temperature (Green and Selman, 2005;Abdul-Mutalib et al, 2012;Arendt et al, 2015;Tóth et al, 2017). Only 40% of food handlers can identify the recommended internal temperature for cooking of poultry and ground beef (Jianu and Chiş, 2012;Feng and Bruhn, 2019).…”
Section: Perceived Barriers To Using Thermometer During Cookingmentioning
confidence: 99%
See 3 more Smart Citations